Model-free rate expression for thermal decomposition processes: The case of microcrystalline cellulose pyrolysis. (1st March 2015) - Samuelsson, Lina N.; Moriana, Rosana; Babler, Matthaus U.; Ek, Monica; Engvall, Klas
Highlights: We derive a model-free rate expression using isoconversional principles. Thermal and kinetic analysis revealed influence of initial sample mass. Derived kinetics, based on dynamic data, can model isothermal cellulose pyrolysis. Abstract: We explore the possibility to derive a completely model-free rate expression using isoconversional methods. The Friedman differential method (Friedman, 1964) and the incremental integral method by Vyazovkin (2001) were both extended to allow for an estimation of not only the apparent activation energy but also the effective kinetic prefactor, defined as the product of the pre-exponential factor and the conversion function. Analyzing experimental thermogravimetric data for the pyrolytic decomposition of microcrystalline cellulose, measured at six different heating rates and three different initial sample masses (1.5–10 mg), revealed the presence of secondary char forming reactions and thermal lag, both increasing with increased sample mass. Conditioning of the temperature function enables extraction of more reliable prefactors and we found that the derived kinetic parameters show weak dependence on initial sample mass. Finally, by successful modeling of quasi-isothermal experimental curves, we show that the discrete rate expression estimated from linear heating rate experiments enables modeling of the thermal decomposition rate without any assumptions regarding the chemical process present. These findings can facilitate the design and optimization of industrial isothermal biomass fed reactors.